Outcomes for potential kidney transplant recipients offered public health service increased risk kidneys: A single‐center experience. Issue 12 (8th November 2018) - Fernandez, Hilda E.; Chiles, Mariana C.; Pereira, Marcus; Husain, Syed Ali; Miko, Benjamin; Baral, Prativa; Dale, Leigh‐Anne; Patel, Shefali; Runge, Brian; Tsapepas, Demetra; Sandoval, Pedro Rodrigo; Ratner, Lloyd E.; et al.
Abstract: Background: Discard rate of Public Health Service Increased Risk (PHS‐IR) organs is high despite the absence of worse kidney transplant outcomes. Methods: We conducted a retrospective, single‐center study of PHS‐IR kidney offers made to kidney transplant‐only potential recipients from 6/2004 to 5/2015. Overall mortality and transplant outcomes between potential recipients were stratified by response to PHS‐IR kidney offers. Cox regression and Kaplan‐Meier analyses of mortality and allograft failure were performed. Results: A total of 2423 potential recipients were offered a PHS‐IR kidney, with 1502 transplanted, with or without a PHS‐IR kidney. Predictors of accepting a PHS‐IR kidney included higher Estimated Post Transplant Survival (EPTS) score, prior kidney transplant, and lower educational achievement on multivariable analysis ( P = 0.025, P = 0.004, P = 0.023). A positive response to a PHS‐IR kidney was associated with lower risk of mortality (3.63% vs 11.6%; aHR 0.467, P = 0.0008). PHS‐IR kidney recipients had decreased risk of allograft loss compared to non‐PHS‐IR recipients ( P = 0.007), though mortality outcomes were not significantly different based on PHS‐IR status ( P = 0.38). No transmission of HIV, HBV, or HCV occurred from PHS‐IR kidney donors in this cohort. Conclusions: Efforts must be made to increase awareness of the beneficial outcomes of PHS‐IR organs to maximize appropriate donor allocation.